Global digital divide: The impact of information and communication technologies (ICT) on economic indicators / Debbra Toria Nipo - Nipo, Debbra Toria (Institute of Graduate Studies, UiTM, 2018)
The advancement of information and communication technology (ICT) over the last decades has brought significant economic and social improvements to both the society and countries. Not only does it revolutionize the global economic structure, ICT is fast becoming a key tool in driving economic growth by promoting productivity and competitiveness, stimulating international trade as well as paving the way for more and better jobs in the market. In the body of literature, there exists a general consensus among researchers that ICT has significant and positive relationship with economic growth. However, most of the evidences come from microeconomic studies, where the firm or countries are typically restricted to specific sectors or regions, or even grouped according to different levels of development. Evidence on impacts of ICT on economic growth across different regions on the other hand, is still scarce and requires further investigation. With the endogenous growth theory as a theoretical basis, this study therefore attempts to analyze further the impact of ICT on economic indicators for five different country groups, namely Africa, America, Arab, Asia and Europe, over a 9-year period of 2006 to 2014. In this study, ICT is defined according to two dimensions - ICT access and usage - where they are proxied by four different measures, namely fixed broadband subscriptions, fixed telephone subscriptions, mobile cellular subscriptions and Internet users.